PENGEMBANGAN BAHAN AJAR SASTRA CERITA RAKYAT NUSANTARA - ANGGRAINI, DESI; Ariesta, Ria; Trianto, Agus (UNIB Press, 2022)
Development of Reader Response-Based Archipelago Folklore Teaching Materials aims to increase students' intellectual activity through archipelago folklore. data, (3) product design, (4) design validation, (5) design improvement, (6) product trial (7) design improvement. Data analysis uses qualitative data analysis techniques, while the validation sheet analysis and questionnaire steps include: converting quantitative data into qualitative, tabulating the data obtained on each aspect, calculating the average score, and changing the average score into categories. Research results shows that 1) the need for teaching materials according to teachers and students, paying attention to: (a) the context of language for various purposes, (b) keeping up with the times, (c) in accordance with the applicable curriculum by raising themes around students, ( d) the relevance between teachers and students in teaching (f) tasks/practices can activate students, (g) material attracts students' interest, is clear, and easy to understand, and (h) relatively 2) describes the teacher's role in learning appreciation of archipelago folklore through reader response model, obtain an overview of student activity in dealing with Indonesian folklore through the reader response model, 3) Product quality based on The results of the validation of material experts based on the percentage of assessment scores obtained an average score of 93.75%, media expert validation of the percentage of assessment scores obtained an average score of 81.66%, 3 educator assessments obtained an average score of 88.59%. Based on the results of the overall validation with an average score that is categorized as very feasible to use.